Analisis Kebutuhan Traktor Tangan (Hand Tractor) Menggunakan Sistem Informasi Geografi di Kecamatan Pringsewu dan Kecamatan Gading Rejo Kabupaten Pringsewu - Setiawan, Fajar Arief; Ridwan, Ridwan; Suharyatun, Siti; Asmara, Sandi (abe.fp.unila.ac.id, 2022)
The application of agricultural mechanization is one of the important components in the agricultural industry that utilizes agricultural tools and machines to improve farming efficiency. Farmers can maximize the energy produced by the machineries to cut the time, production costs and increase production value. The object of this research is Pringsewu and Gading Rejo Subdistricts, Pringsewu District. The suitability analysis of hand tractors was carried out to determine the distribution of areas suitable for hand tractor application. The analysis was carried out by overlaying spatial data in the form of rainfall, slope, soil type, and paddy fields using Quantum GIS 3.16.5 software. The results of the analysis show that Pringsewu Subdistrict has 3 categories of suitability for the application of hand tractors, namely: Very Suitable (SS) 17,43 hectares, Suitable (S) 2.078,92 hectares, and Not Suitable (TS) 710.46 hectares. Gading Rejo Subdistrict has 2 categories, namely: Suitable (S) 3.20,50 hectares and Not Suitable (TS) 696.83 hectares. Analysis of the need for agricultural tools and machinery is carried out to determine the amount of machinery needed in an area. Analysis of the need for hand tractors is carried out to determine the number of needs for hand tractors in an area. The results of the research show that the need for hand tractors in the Pringsewu District was 177 units, while in the Gading Rejo District there were 282 units. Keywords: Agricultural Mechanization, Land Suitability, Overlay Map, Spatial Data, Quantum GIS.